The Use of CERIA E-Module to Enhance Parents’ Knowledge and Family Support Practice among Childhood Cancer Survivors Undergoing Chemotherapy - Utami, Kadek Cahya Utami; Devi, Ni Luh Putu Shinta; Puspita, Luh Mira (Babali Publisher, 2024)
Introduction: Chemotherapy is scientifically demonstrated as an effective modality for childhood cancers. However, despite its therapeutic effects, chemotherapy can induce unpleasant side effects. These adverse effects often cause readmissions and trigger stressful, frightening, and painful experiences. These dreadful conditions may cumulatively affect the quality of life. Family social support has been widely mentioned as a significant factor affecting childhood cancer survivors’ quality of life. That being said, an adequate level of knowledge is needed to achieve the ideal family support for the children. For a long time, the standard method applied for knowledge improvement was direct health education and counseling. However, electronic health education is now considered an excellent alternative to the standard method. This study examined the effect of the CERIA e-module application as an electronic health education media for childhood cancer survivors and their parents and the effectiveness of CERIA e-module in improving parents’ knowledge and family support practice for childhood cancer survivors. Methods: This study is a quasi-experimental study employing a total sampling technique. Thirty participants from Rumah Singgah Yayasan Peduli Kanker Anak Bali were recruited for this study. Results: Findings from this study showed that CERIA e-module is effective in improving parents’ knowledge (p=0.000; p<0.05) and enhancing skills in delivering adequate care and support for children with cancer (p=0.001; p<0.05). Conclusion: Based on the results of this study, the authors suggest that nurses organize novel and creative education media for families with childhood cancer survivors to deliver the health messages more attractively.